TIMP-1 Induces an EMT-Like Phenotypic Conversion in MDCK Cells Independent of Its MMP-Inhibitory Domain - Jung, Young Suk; Liu, Xu-Wen; Chirco, Rosemarie; Warner, Richard B.; Fridman, Rafael; Kim, Hyeong-Reh Choi (PLOS ONE, 2012)
Matrix metalloproteinases (MMPs) and their endogenous inhibitors (TIMPs) regulate epithelial-mesenchymal transition (EMT) critical for the development of epithelial organs as well as cancer cell invasion. TIMP-1 is frequently overexpressed in several types of human cancers and serves as a prognostic marker. The present study investigates the roles of TIMP-1 on the EMT process and formation of the lumen-like structure in a 3D Matrigel culture of MDCK cells. We show that TIMP-1 overexpression effectively prevents cell polarization and acinar-like structure formation. TIMP-1 induces expression of the developmental EMT transcription factors such as SLUG, TWIST, ZEB1 and ZEB2, leading to downregulation of epithelial marker and upregulation of mesenchymal markers. Importantly, TIMP-1′s ability to induce the EMT-like process is independent of its MMP-inhibitory domain. To our surprise, TIMP-1 induces migratory and invasive properties in MDCK cells. Here, we present a novel finding that TIMP-1 signaling upregulates MT1-MMP and MMP-2 expression, and potentiates MT1-MMP activation of pro-MMP-2, contributing to tumor cell invasion. In spite of the fact that TIMP-1, as opposed to TIMP-2, does not interact with and inhibit MT1-MMP, TIMP-1 may act as a key regulator of MT1-MMP/MMP-2 axis. Collectively, our findings suggest a model in which TIMP-1 functions as a signaling molecule and also as an endogenous inhibitor of MMPs. This concept represents a paradigm shift in the current view of TIMP-1/MT1-MMP interactions and functions during cancer development/progression.